CHALLENGES AND PROGRESS IN THE IMPLEMENTATION OF LAWS Nº 10.639/2003 AND Nº 11.645/2008:: PATHS TOWARDS ANTI-RACIST AND INCLUSIVE EDUCATION - Maria Luna Santos, Heloisa; das Graças Andrade Ataíde de Almeida, Maria; Oscar Briones Salazar, Leopoldo; Antonio Ayala Silvera, Luis (Revista Gênero e Interdisciplinaridade, 2025)
This paper analyzes the implementation of Laws No. 10.639/2003 and No. 11.645/2008 in the Brazilian educational system, highlighting their advances, challenges, and potential. These laws aim to incorporate Afro-Brazilian, African, and indigenous history and culture content into school curricula, promoting a more inclusive and anti-racist education. The research, which uses a qualitative approach, uses a bibliographic review and documentary analysis to examine examples of good practices, limitations, and implementation strategies. The results reveal specific advances, such as interdisciplinary pedagogical projects, and government initiatives for teacher training and teaching materials. However, significant challenges persist, including institutional resistance, insufficient teaching resources, and lack of preparation of educators. It is concluded that investments in teacher training, expansion of teaching materials, and strengthening of partnerships with local communities are essential to ensure the transversality and effectiveness of the laws. This study contributes to the debate on public education policies and to the construction of a more equitable society.